2013
DOI: 10.1186/1475-2840-12-35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sitagliptin beyond glycemic control: focus on quality of life

Abstract: BackgroundRecently, incretin hormones, including glucagon-like peptide-1 (GLP-1) analogue and dipeptidyl peptidase-4 (DPP-4) inhibitor, have been found to regulate glucose metabolism. The aim of this study was to elucidate the efficacy and safety of the clinical usage of DPP-4 inhibitors in Japan.MethodsThis study was designed as a prospective, open-label, multi-center trial. Patients with diabetes mellitus type 2 (T2DM) with poor glycemic profiles (HbA1c ≥ 6.2%) in spite of receiving a medical diet, therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
(33 reference statements)
5
35
0
Order By: Relevance
“…Beyond its glycemic control,DPP-4 inhibitors improve blood pressure, lipid profiles, and quality of life (QOL) in patients with T2DM (Kutoh and Yamashita, 2012;Sakamoto et al, 2013). Sitagliptin medication decreased serum levels of total cholesterol and triglyceride (Qin et al, 2005;Monamie et al, 2012;Picatoste et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its glycemic control,DPP-4 inhibitors improve blood pressure, lipid profiles, and quality of life (QOL) in patients with T2DM (Kutoh and Yamashita, 2012;Sakamoto et al, 2013). Sitagliptin medication decreased serum levels of total cholesterol and triglyceride (Qin et al, 2005;Monamie et al, 2012;Picatoste et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonylureas, dipeptidyl peptidase-IV (DPP-IV) inhibitors, and GLP-1 analogs are generally used as insulin secretagogues; however, sulfonylureas increase insulin secretion regardless of glucose level, thereby carrying the risk of promoting hypoglycemia and accelerating the exhaustion of pancreatic b-cells (Pfeifer et al, 1984;Melander et al, 1990), whereas DPP-IV inhibitors and GLP-1 analogs exhibit glucosedependent insulin secretion and carry a low risk of hypoglycemia (Herman et al, 2006;Engel et al, 2010;Bode, 2011). It is widely reported that long-term use of insulin secretagogues lead to reduction in blood hemoglobin A 1c (HbA 1c ) level in human (Charbonnel et al, 2013;Hanefeld et al, 2007;Sakamoto et al, 2013;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other comparative studies reveal comparison of Lipid profiles include a study performed by Chawla S. et al [12] revealed a significant (p<0.01) decrease in High density lipoprotein (HDL-C) & a significant (p<0.01) decrease in Triglyceride, whereas Katsuyama et al [2] had also established that significant differences was seen in effects of Sitagliptin treatment on Another study performed by Sakamoto Y. et al [13] had demonstrated that serum levels of triglycerides and total cholesterol decreased significantly. (p<0.001).…”
Section: Resultsmentioning
confidence: 99%